Georgia Architectucral and Historic Properties Survey of Morven [022] Albany St. Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Morven [022] Albany St. Quitman, Ga. December 1980. One story house of rectangular plan. Gabled roof and shed porch. Interior chimney and shiplap siding. Double hung sash with 2/2 lights. Set on concrete blocks. House appears to have been moved here. Good condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area not extensive enough historically.
Georgia Architectural and Historic Properties Survey of Morven [022] Albany St. Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.15 MB (1,212,126 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Morven, Ga.; Quitman (Ga.)